EFEKTIVITAS PEMBELAJARAN KOOPERATIF DENGAN MENGGUNAKAN MODUL - Tetty Natalia Sipayung; Sinta Dameria Simanjuntak (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
The aims of this research are to determine the effectiveness of cooperative learning by using modules. The type of this research is quantitative research by descriptive method. This research consisting of experiment class and control class. Students in the experimental class are taught by applying cooperative learning using modules while students in control classes are taught by applying conventional learning without modules. The results suggest that cooperative learning using modules is effective. This can be seen from the average percentage of the students  minimum achievement in the control class is 54.92% while in the experimental class is 73.17%. Student activity in the experimental class is excellent with an average score is 4.05 whereas in the control class is good with an average score is 3.7. The ability of teachers in managing learning in the experimental class is very good with an average score is 4.66 whereas in the control class is good with the average score is 4. Thus cooperative learning using the module is effective.